Stressors, Resources, and Stress Responses in Pregnant African American Women: A Mixed-Methods Pilot Study - Giurgescu, Carmen (2013)
This research aimed to develop an initial understanding of the stressors, stress responses, and personal resources that impact African American women during pregnancy, potentially leading to preterm birth. Guided by the ecological model, a prospective, mixed-methods, complementarity design was used with 11 pregnant women and 8 of their significant others. Our integrated analysis of quantitative and qualitative data revealed 2 types of stress responses: high stress responses (7 women) and low stress responses (4 women). Patterns of stress responses were seen in psychological stress and cervical remodeling (attenuation or cervical length). All women in the high stress responses group had high depression and/or low psychological well-being and abnormal cervical remodeling at one or both data collection times. All but 1 woman had at least 3 sources of stress (racial, neighborhood, financial, or network). In contrast, 3 of the 4 women in the low stress responses group had only 2 sources of stress (racial, neighborhood, financial, or network) and 1 had none; these women also reported higher perceived support. The findings demonstrate the importance of periodically assessing stress in African American women during pregnancy, particularly related to their support network as well as the positive supports they receive.